Long-term trends in height, weight and body mass index of children and adolescents in Macao Special Administrative Region (China), 2005–2020 - Qingyuan Li; Yousong Yue (PLoS ONE, 2026)
Objective To assess long-term trends in height, weight and body mass index (BMI) among children and adolescents from 2005 to 2020 in Macao Special Administrative Region (SAR), China. Methods Height, weight and BMI data for Macao children and adolescents aged 6–18 years were obtained from the Physical Fitness Reports of Macao SAR Residents in 2005, 2010, 2015, and 2020. Sex-specific two-way analysis of variance was used to estimate the differences in means. The Bonferroni post hoc test was used for multiple comparisons. Results During the entire period, the average height, weight and BMI increased by 2.1 cm (95% confidence interval (CI): 1.6 to 2.6 cm), 4.0 kg (95% CI: 3.2 to 4.8 kg), and 1.1 kg/m 2 (95% CI: 0.8 to 1.3 kg/m 2 ) for boys and 2.4 cm (95% CI: 1.9 to 2.9 cm), 2.6 kg (95% CI: 1.9 to 3.3 kg), and 0.5 kg/m 2 (95% CI: 0.3 to 0.8 kg/m 2 ) for girls, respectively ( p < 0.001). Boys and girls in most age groups experienced significant increases. The greatest increases in height occurred between 2005 and 2010 in both sexes. The weight and BMI of boys have continued to increase. The weight and BMI of girls continued to increase until 2015, and thereafter declined. Conclusion There were positive long-term trends in growth among Macao children and adolescents since 2005. Sex differences in changes of weight and BMI over the past five years may be related to the pandemic, and efforts are needed by governments and public health departments.